Genome-wide circular RNA profiling and competing endogenous RNA regulatory network analysis provide new insights into the molecular mechanisms underlying early somatic embryogenesis in Dimocarpus longan Lour. (21st March 2022) - Chen, Xiaohui; Xu, Xiaoping; Zhang, Shuting; Munir, Nigarish; Zhu, Chen; Zhang, Zihao; Chen, Yukun; Xuhan, Xu; Lin, Yuling; Lai, Zhongxiong
Abstract: Circular RNAs (circRNAs) are widely involved in plant growth and development. However, the function of circRNAs in plant somatic embryogenesis (SE) remains elusive. Here, by using high-throughput sequencing, a total of 5029 circRNAs were identified in the three stages of longan ( Dimocarpus longan Lour.) early SE. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that differentially expressed (DE) circRNA host genes were enriched in the 'non-homologous end-joining' (NHEJ) and 'butanoate metabolism' pathways. In addition, the reactive oxygen species (ROS) content during longan early SE was determined. The results indicated that ROS-induced DNA double-strand breaks may not depend on the NHEJ repair pathway. Correlation analyses of the levels of related metabolites (glutamate, γ-aminobutyrate and pyruvate) and the expression levels of circRNAs and their host genes involved in butanoate metabolism were performed. The results suggested that circRNAs may act as regulators of the expression of cognate mRNAs, thereby affecting the accumulation of related compounds. A competing endogenous RNA (ceRNA) network of DE circRNAs, DE mRNAs, DE long noncoding RNAs (lncRNAs) and DE microRNAs (miRNAs) was constructed. The results showed that the putative targets of the noncoding RNA (ncRNAs) were significantly enriched in the KEGG pathways 'mitogen-activated protein kinase signaling' and 'nitrogen metabolism'. Furthermore, the expression patterns of the candidate circRNAs, lncRNAs, miRNAs and mRNAs confirmed the negative correlation between miRNAs and ceRNAs. In addition, two circRNA overexpression vectors were constructed to further verify the ceRNA network correlations in longan early SE. Our study revealed the potential role of circRNAs in longan early SE, providing new insights into the intricate regulatory mechanism underlying plant SE.